Implementation of Village Fund Management - Irman Nurhakim; Ivan Yudianto (Universitas Padjadjaran, 2018)
The purpose of This study is to find out how the implementation of village fund management as well as supporting factors and inhibiting factors in the management of village funds. The method used in this research is a qualitative method with interview approach and observation with the responder, that is Head of Village, Village Secretary, Village Treasurer, and Village Consultative Body (BPD). Data analysis is done by data reduction then presents the data and draw conclusions on the data obtained according to the method of data analysis for qualitative research. The results of this study indicate that the implementation of fund management from planning, implementation, administration, reporting, and accountability of the three villages are appropriate with the Regulation of the Minister of Home Affairs Number 113 the Year 2014 concerning Village Financial Management, but in terms of administration for the Panyirapan Village has not been in accordance with regulation, then for reporting the three villages have not been able to report to the regency in a timely manner based on regulations. For most supporting factors in the three villages of human resource training for the village government, understanding in running the Village Financial System application and for the three villages as a whole is still the lack of workers in the field during development activities and the lack of human resources in administration and regulation.